Linear Optical Properties of Beta Barium Borate (β-BaB2O4) Crystal - Awad , Marwan Manhal (International Journal of Psychosocial Rehabilitation, 2020)
In this paper, the linear optical properties of beta barium borate (β-BaB2O4) crystal were studied. The dimensions of the crystal were (4×4×5) mm and the crystal thickness was 5mm. The optical properties include absorbance, transmittance, absorption coefficient, extinction coefficient, refractive index, reflectance, optical conductivity and dielectric constant. The absorption edge of BBO crystal investigated. Band gap energy of BBO crystal obtained from absorption coefficient. The absorption coefficient of BBO crystal at 1064nm was 1.75cm- 1.Theoretically, we calculated the refractive index that depended on the wavelengths. The refractive index was 1.6552 at 1064nm. The reflectance also calculated theoretically for s and p polarization. The relationship between the reflectance and the incident angle from face of the crystal investigated.